2016
DOI: 10.1021/acsnano.6b04606
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in 2D BiSe Bilayers as n Increases in (BiSe)1+δ(NbSe2)n (n = 1–4) Heterostructures

Abstract: (BiSe)(NbSe) heterostructures with n = 1-4 were synthesized using modulated elemental reactants. The BiSe bilayer structure changed from a rectangular basal plane with n = 1 to a square basal plane for n = 2-4. The BiSe in-plane structure was also influenced by small changes in the structure of the precursor, without significantly changing the out-of-plane diffraction pattern or value of the misfit parameter, δ. Density functional theory calculations on isolated BiSe bilayers showed that its lattice is very fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 64 publications
7
33
0
Order By: Relevance
“…The [(BiSe) 1+δ ] 1 [TiSe 2 ] 1 region is remarkably defect free considering the low annealing temperature and short annealing times required to transform from [(BiSe) 1+δ ] 2 [TiSe 2 ] 2 . Antiphase boundaries are present in the BiSe layer, as reported previously. ,, The visible zone axis changes orientations layer to layer, consistent with turbostratic disorder. The Bi 2 Se 3 region contains more defects, including regions where it appears that BiSe monolayers separate Bi 2 Se 3 layers.…”
Section: Resultssupporting
confidence: 86%
“…The [(BiSe) 1+δ ] 1 [TiSe 2 ] 1 region is remarkably defect free considering the low annealing temperature and short annealing times required to transform from [(BiSe) 1+δ ] 2 [TiSe 2 ] 2 . Antiphase boundaries are present in the BiSe layer, as reported previously. ,, The visible zone axis changes orientations layer to layer, consistent with turbostratic disorder. The Bi 2 Se 3 region contains more defects, including regions where it appears that BiSe monolayers separate Bi 2 Se 3 layers.…”
Section: Resultssupporting
confidence: 86%
“…This is consistent with previous studies, which concluded that antiphase boundary formation in BiSe localized the Bi valence electron, inhibiting interlayer charge transfer . However, a recent study of (BiSe) 1+ δ (NbSe 2 ) n compounds with thicker NbSe 2 layers suggests that the situation is more complicated . The BiSe lattice changes from rectangular to square for values of n greater than 1, correlated with a significant reduction in the number of antiphase boundaries, but the magnitude of interlayer charge transfer does not appear to change.…”
Section: Resultssupporting
confidence: 91%
“…The thickness of the blocks and their [100] orientation were constant in the whole area of investigation. The synthesis technique used here leads to a more uniform structure than the layer-bylayer vapour deposition employed by Mitchson et al 42,43 The structure of (BiSe)1.10NbSe2, refined (Fig. 4a) using the (BiSe)1.09TaSe2 35,40 model as a starting point, is overlaid on the images.…”
Section: Structural Analysis Of (Bise)110nbse2mentioning
confidence: 99%